Hebella eximia Fraser 1944 - Calder, Dale R.; Choong, Henry H. C. (Zenodo, 2018)
Hebella eximia Fraser, 1944a Hebella (?) eximia Fraser, 1944a: 207, pl. 39, figs. 185a, b. Holotype. MCZ-IZ 9067: Dominica, USCSS Blake Sta. 185, 15°24’55”N, 61°27’10”W, 333 fm (609 m), 27 January 1879, coll. A. Agassiz; ethanol (specimen now missing from its vial). Type locality. Dominique (Dominica): 15°24’55”N, 61°27’10”W, 333 fm (609 m) (Fraser 1944a). Current status. Species inquirenda . Remarks. While no name-bearing types of Hebella (?) eximia were designated by Fraser (1944a), the online catalogue at MCZ records type material of the species in the collection (MCZ-IZ 9067). That record does not specify the number of colonies, but Fraser’s (1944a) description was of a single colony. No types or other specimens were located elsewhere, including the Fraser Hydroid Collection at the RBCM. The MCZ specimen, apparently the holotype by monotypy (ICZN Art. 73.1.2), is now missing from its bottle. The vial originally containing it was carefully checked twice during this study, but no hydroids of H. eximia were found. Fraser (1944a) founded Hebella eximia in his book on hydroids of the western North Atlantic. No gonosome was present, and he was uncertain of its generic affinities. Boero et al . (1997) referred it to the synonymy of H. scandens (Bale, 1888), given the resemblance of its trophosome to that species. Their conclusion has been upheld in the current WoRMS list. Based on Fraser’s account of the morphology of its hydrothecae, however, and the considerable depth from which it was collected, it may well be distinct. It is held here to be a species inquirenda . With the holotype now missing, designation of a neotype, following provisions of the ICZN, seems desirable if the species is re-discovered. Published as part of Calder, Dale R. & Choong, Henry H. C., 2018, Names of hydroids (Cnidaria, Hydrozoa) established by Charles McLean Fraser (1872 - 1946), excluding those from Allan Hancock Expeditions, pp. 1-83 in Zootaxa 4487 (1) on page 40, DOI:10.11646/zootaxa.4487.1.1, http://zenodo.org/record/1456161